2023
DOI: 10.1038/s41388-023-02594-w
|View full text |Cite
|
Sign up to set email alerts
|

The pseudokinase NRBP1 activates Rac1/Cdc42 via P-Rex1 to drive oncogenic signalling in triple-negative breast cancer

Abstract: We have determined that expression of the pseudokinase NRBP1 positively associates with poor prognosis in triple negative breast cancer (TNBC) and is required for efficient migration, invasion and proliferation of TNBC cells in culture as well as growth of TNBC orthotopic xenografts and experimental metastasis. Application of BioID/MS profiling identified P-Rex1, a known guanine nucleotide exchange factor for Rac1, as a NRBP1 binding partner. Importantly, NRBP1 overexpression enhanced levels of GTP-bound Rac1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Previously, we demonstrated that PEAK1 gene knock-out significantly inhibited growth of MDA-MB-231 TNBC xenografts, as well as experimental metastasis of these cells in a tail vein injection assay 7 . To test RA306, we utilized the highly metastatic variant of this cell line, MDA-MB-231-HM 35 , so that we could assay metastatic spread from the primary tumour. In addition, we generated PEAK1-deficient MDA-MB-231-HM cells via CRISPR editing (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we demonstrated that PEAK1 gene knock-out significantly inhibited growth of MDA-MB-231 TNBC xenografts, as well as experimental metastasis of these cells in a tail vein injection assay 7 . To test RA306, we utilized the highly metastatic variant of this cell line, MDA-MB-231-HM 35 , so that we could assay metastatic spread from the primary tumour. In addition, we generated PEAK1-deficient MDA-MB-231-HM cells via CRISPR editing (Supp.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we assumed positive regulation of Rac1 by Cdc42 in our model. However, the opposite regulation (from Rac1 to Cdc42) cannot be excluded because bidirectional crosstalk is possible through the interaction of Rac1 and Cdc42 with their common GEFs [ 10 , 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…New discoveries regarding the mechanisms [35,36], biomarkers [12], and expression patterns [37] of breast cancer are emerging with the use of intrinsic subtyping tools, speci cally the commonly used PAM50 and AIMS models. However, misclassi cation of intrinsic subtypes could result in decreased research accuracy.…”
Section: Discussionmentioning
confidence: 99%